2018
DOI: 10.1038/s41598-018-21517-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Contents in Matrix Vesicles Produced by Growth Plate Chondrocytes are Cell Maturation Dependent

Abstract: Chondrocytes at different maturation states in the growth plate produce matrix vesicles (MVs), membrane organelles found in the extracellular matrix, with a wide range of contents, such as matrix processing enzymes and receptors for hormones. We have shown that MVs harvested from growth zone (GC) chondrocyte cultures contain abundant small RNAs, including miRNAs. Here, we determined whether RNA also exists in MVs produced by less mature resting zone (RC) chondrocytes and, if so, whether it differs from the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…Functional analysis showed that these miRNAs influenced key functions for cartilage development and extracellular matrix control such as stem cell regulation, focal adhesion, and cell cycle control. These data further support the evidence that extracellular miRNAs play a key role for cell-cell communication and cell proliferation and differentiation in the growth plate [37].…”
Section: Mirnas Regulating the Growth Platesupporting
confidence: 87%
“…Functional analysis showed that these miRNAs influenced key functions for cartilage development and extracellular matrix control such as stem cell regulation, focal adhesion, and cell cycle control. These data further support the evidence that extracellular miRNAs play a key role for cell-cell communication and cell proliferation and differentiation in the growth plate [37].…”
Section: Mirnas Regulating the Growth Platesupporting
confidence: 87%
“…For miR-122-5p, The Human miRNA Tissue Atlas 26 (website https://ccb-web.cs.uni-saarland.de/tissueatlas/ ) Variance Stabilised Normalisation (VSN) relative data 27 showed that miR-122-5p is expressed in liver and bone, as well as a number of other tissues, but hardly present in bone marrow. However, recently, it has been reported in rats that microvesicles produced by resting zone chondrocytes are over 800-fold enriched in hsa-miR-122-5p than the producing cells 28 , whereas miR-122-5p is not present in microvesicles from growth zone chondrocytes. This observation raises the novel possibility that the changes in serum hsa-miR-122-5p levels in osteoporosis/osteopaenia patients might reflect changes in chondrocyte-derived microvesicles in the blood.…”
Section: Discussionmentioning
confidence: 96%
“…Matrix vesicles also mediate a wide range of functions besides initiation of mineralization, such as cell-cell communication, depending on their distinct contents and properties. These may include different microRNA species (miR-122-5p vs. miR-150-5p), different specific phospholipids, different activities of alkaline phosphatase and phospholipase A2, different membrane stiffness, and different membrane receptors ( 116 ). Due to these distinct functions and properties, matrix vesicles are now described by a wide variety of names: microvesicles, extracellular membrane vesicles, ectosomes, extracellular vesicles, microparticles, and exosomes, depending on cells of origin, tissue location, and the investigator's field of science.…”
Section: Matrix Vesiclesmentioning
confidence: 99%